Seric concentrations of copper, chromium, manganesum, nickel and selenium in aerobic, anaerobic and mixed professional sportsmen - Maynar, M.; Llerena, F.; Bartolomé, I.; Alves, J.; Robles, M. C.; Grijota, F.-J.; Muñoz, D. (Journal of the International Society of Sports Nutrition, 2018)
Background: The aim of the present study was to determine changes in serum concentrations of trace elements Cooper (Cu), Chromiun (Cr), Manganesum (Mn), Nickel (Ni) and Selenium (Se) in high-level sportsmen. Methods: Eighty professional athletes of different metabolic modalities, were recruited before the start of their training period. Thirty one sedentary participants of the same geographic area constituted the control group. Cu, Cr, Mn, Ni and Se analysis was performed by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Results: Higher concentrations of Cr (p < 0.001), Mn (p < 0.085), and Ni (p < 0.001) were found in sportsmen in comparison to controls, inversely, Se values were lower (p < 0.001) among sportsmen. When sportsmen were classified by metabolic modalities, it was found that aerobic-anaerobic group had higher (p < 0.01) Cu concentrations than controls and the other sportsmen. The highest Cr values were found in aerobic participants. For Mn, the major levels were found in aerobic and aerobic-anaerobic groups as well (p < 0.001). The lowest Se levels were found among anaerobic sportsmen (p < 0.001). Conclusion: This research showed that daily, continuum physical training induced alterations in serum essential minerals concentrations, as well as that these changes can be dependent of the exercise modality practiced.